Torsional Vibration Characteristics Analysis and Parameter Optimization of Parallel Hybrid Electric Vehicle Powertrain - Zhiyong Wen; Baoyu Guo; Hongfei Nie; Lin Chen; Shaofei Liu; Zhengfeng Yan (Shock and Vibration)
The diversity of vibration excitation sources and working modes in hybrid electric vehicles makes the problem of torsional vibration in the powertrain more prominent. To address the intricate torsional vibration issues in hybrid electric vehicles, this study analyzes the vibration characteristics of the powertrain and optimizes the parameters of the torsional damper. A torsional vibration model of the parallel hybrid powertrain was established, and the model’s validity was verified through resonance analysis of its inherent and excitation characteristics. The vibration suppression properties of the torsional damper were examined under acceleration, idle loading, and engine starting conditions, leading to the establishment of a parameter optimization scheme considering multiple working conditions. Following optimization, the root mean square value of the powertrain’s angular acceleration decreased by over 20% under the three working conditions, confirming the efficacy of the proposed optimization scheme.